A Review of Intermittent Poisoning to Mitigate Toxic Plant-Induced Disease in Livestock - Bryan L. Stegelmeier; T. Zane David; Kip E. Panter; Kevin D. Welch; Edward L. Knoppel (Veterinary Sciences)
Poisonous plants affect livestock and wildlife and in addition to animal disease, they often inhibit the productive use of feeds and natural resources. For some plants, intermittent or cyclic grazing may allow the use of contaminated forages or infested pastures or ranges while avoiding permanent effects of poisoning. The objective of this review is to present several toxic plants for which intermittent poisoning might be an effective management tool. Additionally, as intermittent exposures present risks, those risks will be discussed, and signs of impending problems identified. Additional plants that mechanistically have potential for becoming less problematic via intermittent exposure will also be discussed. Lastly, toxic plants to which any exposure causes permanent or fatal damage or those that might result in cumulative damage with repeated exposures will also be discussed.